(untitled) - Lynch, Kenneth (London/New York, 2005)
This introduction to the relationships between rural and urban places shows that not all their aspects are as obvious as migration from country to city.
Keywords: Rural-urban relations,Developing countries; Developing countries,Economic conditions; Textbooks,Textbooks